2014
DOI: 10.1371/journal.pone.0083338
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Localization and Chorion Thinning among Preterm Premature Rupture of Membranes

Abstract: ObjectiveBacterial colonization of the fetal membranes and its role in pathogenesis of membrane rupture is poorly understood. Prior retrospective work revealed chorion layer thinning in preterm premature rupture of membranes (PPROM) subjects. Our objective was to prospectively examine fetal membrane chorion thinning and to correlate to bacterial presence in PPROM, preterm, and term subjects.Study DesignPaired membrane samples (membrane rupture and membrane distant) were prospectively collected from: PPROM = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 36 publications
1
44
0
5
Order By: Relevance
“…The ELGAN studies constituted a large effort that systematically identified bacteria from PTB placentas under this assumption (Olomu et al 2009; Onderdonk et al 2008a,b). However, there is increasing recognition of a large discordance between the presence of bacteria as per culture-based diagnoses and clinical outcome (Watts et al 1992; Pettker et al 2007; Buhimschi et al 2009; Han et al 2009; Leviton et al 2010; Stout et al 2013; Combs et al 2014; Fortner et al 2014). In fact, the presence of placental or membrane bacteria in the absence of histological infection has been discovered repeatedly over the last few decades (Hillier et al 1988; Steel et al 2005; Redline 2007; Stout et al 2013; Fortner et al 2014).…”
Section: The Placental Microbiomementioning
confidence: 99%
“…The ELGAN studies constituted a large effort that systematically identified bacteria from PTB placentas under this assumption (Olomu et al 2009; Onderdonk et al 2008a,b). However, there is increasing recognition of a large discordance between the presence of bacteria as per culture-based diagnoses and clinical outcome (Watts et al 1992; Pettker et al 2007; Buhimschi et al 2009; Han et al 2009; Leviton et al 2010; Stout et al 2013; Combs et al 2014; Fortner et al 2014). In fact, the presence of placental or membrane bacteria in the absence of histological infection has been discovered repeatedly over the last few decades (Hillier et al 1988; Steel et al 2005; Redline 2007; Stout et al 2013; Fortner et al 2014).…”
Section: The Placental Microbiomementioning
confidence: 99%
“…Essa situação pode ser o reflexo da utilização de antibióticos no tratamento empírico da sintomatologia genitourinária, sem confirmação laboratorial da colonização. Nesses casos, a antibioterapia erradica as bactérias, mas poderá não ser o suficiente para travar o processo inflamatório subjacente 14,15 . Estudos demonstraram que, apesar da presença de bactérias em 80% das RPM-PT, esta por si só não é suficiente para causar PPT, tendo sido identificada em membranas fetais de grávidas a termo em trabalho de parto ou não 14,15 .…”
Section: Discussionunclassified
“…Nesses casos, a antibioterapia erradica as bactérias, mas poderá não ser o suficiente para travar o processo inflamatório subjacente 14,15 . Estudos demonstraram que, apesar da presença de bactérias em 80% das RPM-PT, esta por si só não é suficiente para causar PPT, tendo sido identificada em membranas fetais de grávidas a termo em trabalho de parto ou não 14,15 . No entanto, demonstramos uma elevação significativa dos parâmetros infecciosos (PCR e leucócitos) no grupo PPTe, reforçando, dessa forma, os dados existentes na literatura 5-7 que apontam para um eventual processo inflamatório sistémico, e não localizado, como um dos potenciais fatores para o desencadear de todo o processo do trabalho de parto pré-termo espontâneo.…”
Section: Discussionunclassified
“…We have previously demonstrated that the quantity of bacteria present in the fetal membranes is correlated with chorion thinning, suggesting that bacterial presence may incrementally evoke a host response that leads to chorion cell death and tissue degradation 94 . There is now evidence that the dose and variation of the MBA of U. parvum might affect the severity of chorioamnionitis in pregnant sheep 95 .…”
Section: Commentmentioning
confidence: 99%